Essays on IFRS and investment - Santana, Verônica de Fátima (2019)
This research investigates the role of IFRS on investment, both at the macro level, studying cross-border foreign investment, and at the micro level, studying firm-level investment. The IFRS proponents argue it provides financial information not only comparable across different countries, but also of high quality, minimizing constraints and facilitating investment allocation efficiency. Divided into three different essays, this dissertation evaluates this proposition analyzing the role of IFRS in the interdependent dynamics of cross-country capital flows, in the sensitivity of foreign investment to global financial shocks in Latin America, and in the efficiency of firm-level capital allocation. The first essay studies the interaction between the attraction of capital flows among neighbor countries and their decision to adopt IFRS. Estimating a spatial autoregressive model I show that higher foreign direct investment inflows to a given country imply in higher inflows to its neighbors, and the adoption of IFRS reinforces this. This suggests that, in terms of foreign capital attraction, the more countries adopt IFRS the more advantageous it is for its neighbors also to become adopters. The second essay focuses on the moderating effect of IFRS for the impact of international market uncertainty on the volatility of capital flows in Latin America. Analyzing Argentina, Brazil, Chile, Colombia, Mexico, and Peru via a panel FGLS model, the results show that although IFRS is related to large and more volatile foreign investment inflows, there is some evidence that the adoption minimizes the effects of international uncertainty shocks. Finally, the third essay studies the role of IFRS to ease firms financing constraints along with financial development, via the estimation of an Euler equation investment model. The results show IFRS adoption is capable of minimizing firms\' financing constraints decreasing the cost of external capital. Firms in countries with both low economic and financial development but adopting IFRS have similar financing constraints levels as firms in high financial or economic development countries who do not adopt IFRS. Taken together, the results are consistent with the hypothesis that higher quality accounting information can improve investment decisions. Increased attraction of capital flows, decreased sensitivity to uncertainty shocks in Latin America, and minimized firms\' financing constraints indicate IFRS adoption is able to improve investment allocation decisions. These results are important mainly from a policy perspective, showing IFRS can have positive effects on investment allocation efficiency, which is expected to improve economic performance and, consequently, growth.